Hubungan Pajanan Pestisida Organofosfat terhadap Jumlah Leukosit dalam Darah Petani Penyemprot di Desa Sumberejo Kecamatan Ngablak - Ana Qomariah; Onny Setiani; Hanan Lanang Dangiran (Jurnal Kesehatan Masyarakat (Undip), 2017)
Background: The role of pesticides in agricultural systems is inseparable without the use of pesticide development of pests can not be controlled so it will have an impact on the decline in the quality of agricultural produce. Organophosphates are the most toxic insecticides. Pesticides can cause abnormalities in the blood profile because it can interfere with blood-forming organs, the process of formation of blood cells and also the immune system. The purpose of the research was to analyze the relationship of pesticide exposure are organophosphate against the number of leukocytes in the blood farmers sprayers in Sumberejo Village.Methods: This type of research was a correlational approach using methods cross sectional with a population that is a sprayers farmers use pesticide of organophosphate  in Sumberejo village, district of Ngablak with a total sample of research as much as 43 farmers.Results: Chi-Square test results shows the results of the relationship between the working periode (p = 0.560), work (p = 0.599), spraying frequency (p = 0.098), use of the APD (p = 0.860), Kolinesterase levels (p = 0.587) against the number of leukocytes in the blood farmers sprayers.Conclusions: In this study is there is no relationship betwen pesticide exposure history organophosphate against the number of leukocytes blood farmers sprayers in Sumberejo Village, District Ngablak . Increased knowledge of pesticides as well as the importance of the use of full APD advised still carried out by the department of health.